The Challenges of Higher Education in Growing Dialogue Culture and Understanding Cultural Pluralism - Obasa, Desmond; Adebule, Jumoke (Jurnal Ilmiah Peuradeun, 2017)
The contemporary world is increasingly multicultural and the identity crisis resulting from this sometimes threatens sustainable human development. Nigeria is a plural society in terms of its multi-ethnic and multi-religious nature. Of all the federal democracies in the world, only India can match Nigeria’s cultural complexity. If well managed, this factor of unity in diversity would have been a major asset to the Nigerian state, but the contrary is the case. Nigeria’s cultural diversity is politicized and exploited by the elite in such a way that retards the nation’s growth and progress. This makes the promotion of understanding and dialogue to be a prime issue in the management of multiculturalism, global peace and security. This paper attempts to answer these questions by taking a critical look at the situations in Nigeria – one of the most culturally-complex countries in the world. The paper is divided into three parts. In the last part, which is actually the fulcrum of the presentation, the point is made that these challenges notwithstanding; the Nigerian universities still manage to make some outstanding contributions in the direction of promoting dialogue among the contending forces in the country. The Nigerian case study is internationally instructive.